Changes in the Home Range of Bornean Orangutans (Pongo pygmaeus wurmbii) Before and After Forest Fires at Tuanan Research Station, Central Kalimantan - Hasan, Silvia; Sri Suci Utami Atmoko (Universitas Nasional Jakarta, 2025)
The Bornean orangutan (Pongo pygmaeus wurmbii), an endangered species native to the tropical forests of Borneo, plays a crucial role in the ecosystem as a keystone species and seed disperser. However, habitat degradation, particularly from forest fires, poses a significant threat to their survival. This study investigates the impact of forest fires on the home ranges of Bornean orangutans at the Tuanan Orangutan Research Station (TORS), Central Kalimantan, Indonesia. Data were collected before and after the 2019 forest fire, focusing on changes in orangutan movement patterns and their responses to altered fruit availability. The results showed that, following the fire, most observed individuals decreased their home range size, except for the flanged male (Dado) and the adult female (Juni), who expanded their home ranges. The forest fire led to a significant reduction in fruit tree productivity, which was reflected in the fluctuating fruit availability index (FAI). Additionally, smoke from the fire disrupted pollination, further impacting fruit production and orangutan foraging behavior. Kernel Density Estimator (KDE) analysis revealed changes in the movement paths and home-range sizes of the orangutans before and after the fire. These findings highlight the adaptability of orangutans to habitat changes induced by fire, and the importance of understanding how fire-related environmental changes affect orangutan survival and behavior. The study underscores the need for practical conservation efforts to mitigate the effects of habitat degradation and maintain food resources for orangutans in post-fire landscapes.